The Protective Effects of Social Support on Hypertension Among African American Adolescents Exposed to Violence - Hsieh, Hsing-Fang (Journal of interpersonal violence, 2022)
African Americans develop hypertension earlier in life than Whites and the racial/ethnic disparities in blood pressure level can appear as early as adolescence. Violence victimization, a prevalent environmental stressor among inner-city youth, may play a role in such disparities. In a sample of inner-city youth in the United States, the current study examines the relationship between violence victimization and hypertension while investigating the role of social support in moderating that relationship. We analyzed eight waves of data from a longitudinal study of African American youth (n = 353, 56.7% female) from mid-adolescence (9th grade, mean age = 14.9 years old) to emerging adulthood (mean age = 23.1 years old) using probit regression. Higher levels of self-reported violence victimization during ages 14?18 was associated with more reports of hypertension during ages 20?23, after adjusting for sex, socioeconomic status, substance use, and mental distress. The relationship of violence victimization with hypertension was moderated by friends? support, but not parental support. The association between victimization and hypertension was weaker and non-significant among individuals with more peer support compared to those with less support. Researchers have reported many instances of associations of early violence exposure to later risk for hypertension; however, most have focused on childhood maltreatment or intimate partner violence. We extend these findings to violence victimization in an African American sample of youth from adolescence to early adulthood, while examining social support modifiers. The disparity in African American hypertension rates relative to Whites may partly be explained by differential exposure to violence. Our findings also suggest that having supportive friends when faced with violence can be beneficial for young adulthood health outcomes.